Survival and growth responses of snakehead fish Channa striata Bloch. juvenile in aerated and unaerated acid sulfate water - Purnamawati, ,; Djokosetiyanto, Daniel; Nirmala, Kukuh; Surawidjaja, Enang Harris; Affandi, Ridwan (Jurnal Akuakultur Indonesia, 2017)
ABSTRACT  The aim of the research was to analyze survival rate, specific growth rate, albumin, and feed efficiency and physiological (blood glucose, cortisol, dan haemoglobin) responses of snake head fish juvenil that reared at aerated and unaerated of tidal land water have been conducted in the laboratory. Experiments using completely randomized design with aerated and unaerated as a treatment, and each treatment has twelve replications. The snakehead fish juvenil wich length 2.4±0.2 cm and weight of 0.21±0.05 g reared in the aquarium that are size 30×25×35 cm (water volume 25 L) with a stocking density 2 juvenile/L, for 40 days. The fishes were fed with commercial feed with protein content about 40%, feeding two times a day (morning and afternoon) were at satiation. Replacement of water done every two days about 10% of the total water volume in the aquarium. The results showed that unaerated median significantly affected to biometric and physiological response of juvenile of snake head fish. The media un-aerated gives the best results shown by the higher value of survival (92%), specific growth rate (6.73%/ day), feed efficiency (78.22%), protein retention (41.91%), energy retention (30.81%) value of albumin (6.60 g/100 mL) and the haemoglobin (5.58 g/dL), and have the lowest value of cortisol (21.49 ng/L) and blood glucose (43.36 mg/100 mL). Keywords: acid sulfate water, growth rate, aeration, Channa striata   ABSTRAK  Penelitian ini bertujuan untuk menganalisis respons kelangsungan hidup, pertumbuhan spesifik, albumin, dan efisiensi pakan dan fisiologis (kortisol, glukosa darah, dan hemoglobin) juvenil ikan gabus yang dipelihara dengan dan tanpa aerasi pada media air rawa pasang surut. Penelitian menggunakan rancangan acak lengkap dengan aerasi dan tanpa aerasi sebagai perlakuan, dan masing-masing perlakuan memiliki 12 ulangan. Juvenil ikan gabus berukuran panjang 2,4±0,3 cm dan bobot 0,21±0,03 g dipelihara dalam akuarium 30×25×35 cm (volume 25 L) dengan padat tebar 2 ekor/L, selama 40 hari. Ikan diberi pakan berupa pakan komersial dengan kadar protein ±40%, pemberian pakan dua kali sehari (pagi dan sore) at satiation. Penggantian air dan penyiponan dilakukan dua hari sekali sebanyak 10% dari volume total dalam akuarium. Hasil penelitian menunjukkan bahwa perlakuan tanpa aerasi berpengaruh nyata terhadap respons biometrik dan fisiologis juvenil ikan gabus. Media tanpa aerasi memberikan hasil yang lebih baik ditunjukkan oleh kelangsungan hidup (92%), laju pertumbuhan spesifik (6,73%/ hari), efisiensi pakan (78,22%), retensi protein (41,91%), retensi energi (30,81%), kadar albumin (6,60 g/100 mL), dan hemoglobin (5,85 g/dL) yang lebih tinggi, sedangkan kadar kortisol (219 ng/L) dan glukosa darah (43,36 mg/100 mL) yang terendah. Kata kunci: media sulfat masam, pertumbuhan, aerasi, Channa striata